Principal Strategies for Teacher Professional Development at TK IT Al Ittihad Pekanbaru - Afriliana; Enung Hasanah; Muhammad Zuhaery (Sakura Digital Nusantara, 2026)
Teacher professional development is essential for improving the quality of early childhood education and requires effective principal strategies to support continuous professional learning. However, evidence on such strategies in integrated Islamic early childhood education settings remains limited. This study aimed to analyse principal strategies for teacher professional development at TK IT Al Ittihad Pekanbaru, Indonesia. A descriptive qualitative single-case study was conducted involving four purposively selected participants, comprising the principal, vice principal, and two teachers. Data were collected through semi-structured interviews, non-participant observations, and document analysis, and analysed using Braun and Clarke’s reflexive thematic analysis supported by ATLAS.ti 9. The findings revealed eight interconnected themes: strategic planning, teacher professional development initiatives, competency strengthening, professional learning culture, monitoring and evaluation, follow-up actions, supporting factors, and implementation barriers. The findings suggest that, within the context of TK IT Al Ittihad Pekanbaru, teacher professional development was perceived to be supported through interconnected practices involving instructional leadership, collaborative professional learning, continuous improvement, and the integration of Islamic values. These findings contribute to the educational leadership literature by providing contextual evidence on principal strategies for teacher professional development in integrated Islamic early childhood education settings.